A “Candidatus Liberibacter asiaticus”-secreted polypeptide suppresses plant immune responses in Nicotiana benthamiana and Citrus sinensis - Shen, Pan; Li, Xueyi; Fu, Shimin; Zhou, Changyong; Wang, Xuefeng (Frontiers in Plant Science, 2022)
Citrus Huanglongbing (HLB), known as the most economically devastating disease in citrus industry, is mainly caused by phloem-restricted Gram-negative bacterium “Candidatus Liberibacter asiaticus” (CLas). To date, CLas is still unculturable in vitro, which has been dramatically delaying the research on its pathogenesis, and only few Sec-dependent effectors (SDEs) have been identified to elucidate the pathogenesis of CLas. Here, we confirmed that a CLas-secreted Sec-dependent polypeptide, namely SECP8 (CLIBASIA_05330), localized in nucleus, cytoplasm and cytoplasmic membrane, and showed remarkably higher transcript abundance in citrus than in psyllids. Potato virus X (PVX)-mediated transient expression assays indicated that mSECP8 (the mature form of SECP8) suppressed pro-apoptotic mouse protein BAX and Phytophthora infestans elicitin INF1-triggered hypersensitive response (HR) associated phenotypes, including cell death, H2O2 accumulation and callose deposition. Intriguingly, mSECP8 also inhibited SDE1 (CLIBASIA_05315)-induced water-soaked and dwarfing symptoms in Nicotiana benthamiana. In addition, mSECP8 can promote the susceptibility of transgenic Wanjincheng orange (Citrus sinensis) to CLas invasion and further HLB symptom development, and it contributes to the proliferation of Xanthomonas citri subsp. citri (Xcc). Moreover, the expression of ten systemic acquired resistance (SAR)-related genes were significantly down-regulated in mSECP8 transgenic citrus than those in wide-type (WT) plants. Overall, we propose that mSECP8 may serve as a novel broad-spectrum suppressor of plant immunity, and provide the first evidence counteractive effect among CLas effectors. This study will enrich and provide new evidences for elucidating the pathogenic mechanisms of CLas in citrus host.